THE POSITION OF RAILWAY LINES AND RAILWAY STATIONS IN PRIANGAN URBAN SPATIAL PLANNING IN THE 19TH TO 20TH CENTURIES - Falah, Miftahul; Herlina, Nina; Muhsin, Mumuh; Sofianto, Kunto (Paramita: Historical Studies Journal, 2018)
In relation to urban spatial planning, it is thought-provoking and substantial to study the development of railway lines and stations in Priangan in the 19th to 20th century. The issues discussed in this research are how to build a railway line when it had to pass through urban areas? And how to locate a railway station in order to be easily accessed from all corners of the city without disrupting the users of land transportation routes. To examine the issues, a historical study is conducted by employing historical method comprising heuristics, criticism, interpretation, and historiography. The result of the research demonstrates that the railway line passing through the urban areas was built in the areas with hardly any settlements; and in big cities, a bridge (viaduct) was specially built for a railway line in order not to obstruct the land transportation routes. The railway line, however, was not too far from the city center, so the railway station was built in a location easily accessible from and to all the corners of the city. Dalam kaitannya dengan tata ruang kota, pembangunan jalur dan stasiun kereta api di Priangan pada abad XIX-XX penting dan menarik untuk dikaji. Permasalahannya adalah bagaimana jalur kereta api dibangun ketika harus melewati kawasan perkotaan?, dan bagaimana penempatan stasiun kereta api sehingga dapat dijangkau dan menjangkau seluruh pelosok kota tanpa mengganggu pengguna jalur transportasi darat? Untuk menjawab permasalahan tersebut, dilakukan penelitian sejarah dengan menerapkan metode sejarah yang meliputi empat tahap, yakni heuristik, kritik, interpretasi, dan historiografi. Hasil penelitian menunjukkan bahwa jalur kereta api yang melewati kawasan perkotaan dibangun di kawasan yang masih jarang pemukiman dan di kota besar dibuatkan jembatan (viaduct) sehingga tidak mengganggu jalur transportasi darat. Namun demikian, jalur tersebut tidak terlalu jauh dari pusat kota sehingga stasiun kereta api dibangun di suatu lokasi agar dengan mudah dapat dijangkau dari dan ke pelosok kota.